2020
DOI: 10.1111/eth.13117
|View full text |Cite
|
Sign up to set email alerts
|

Measuring personality traits in Eurasian red squirrels: A critical comparison of different methods

Abstract: Animal personality, behavioural differences among individuals which are consistent through time and contexts, is generally described by one or more traits. Different methods are used to measure these traits, such as behavioural observations and trapping indices. Comparing several methods allows to validate different tests and to better identify which aspect of an animal's personality is being measured. Here, we measured activity, exploration and immobility of Eurasian red squirrels (Sciurus vulgaris) using obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 100 publications
3
20
0
Order By: Relevance
“…We acknowledge that our local survival estimate is influenced by recapture probability and potential dispersal (emigration) of marked animals, but since both annual recapture probabilities and site-fidelity of adult red squirrels are high (for detailed analyses and discussion see Wauters et al 2004, 2008and Santicchia et al 2018b), we are confident that our estimate mostly captures actual survival rather than dispersal. A different source of bias in annual survival estimates could be due to the parasite affecting host behaviour and/or its willingness to enter a trap, measured as trappability (Santicchia et al 2018b(Santicchia et al , 2021. As mentioned above, we indeed found that infection by alien S. robustus reduced host activity, an energetically costly personality trait (Santicchia et al 2020).…”
Section: Discussionsupporting
confidence: 69%
“…We acknowledge that our local survival estimate is influenced by recapture probability and potential dispersal (emigration) of marked animals, but since both annual recapture probabilities and site-fidelity of adult red squirrels are high (for detailed analyses and discussion see Wauters et al 2004, 2008and Santicchia et al 2018b), we are confident that our estimate mostly captures actual survival rather than dispersal. A different source of bias in annual survival estimates could be due to the parasite affecting host behaviour and/or its willingness to enter a trap, measured as trappability (Santicchia et al 2018b(Santicchia et al , 2021. As mentioned above, we indeed found that infection by alien S. robustus reduced host activity, an energetically costly personality trait (Santicchia et al 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Trappability is associated with space use in several rodents species (25,30,58) and may therefore suggest that individuals who are more active have a higher risk to become infected due to a larger exposure rate to different infected environments. Nonetheless, the link between exploration, measured in an open field arena and trappability is not always clear or present (108)(109)(110). Vanden Broecke et al (58,79), found no correlation between exploration and trappability in M. natalensis which may suggest that this explanation is not very likely.…”
Section: Co-infection Patterns and Behaviormentioning
confidence: 97%
“…Most animals were trapped both before, during and after space use parameters were determined and some traps in which they were caught were outside the estimated home range area (Santicchia et al 2018). Moreover, we are confident that our standardised methods of pre-baiting traps and seasonally spaced multiple days CMR sessions strongly reduced any potential bias in trappability [see also Michelangeli et al 2016 in delicate skink (Lampropholis delicata); Jolly et al 2019 in grassland melomys (Melomys burtoni)] as discussed in detail in previous studies on red squirrels (Wauters et al 2008;Santicchia et al 2018Santicchia et al , 2020. Future research with the use of GPS-collars, which provide continuous animals' locations and complete movements recordings (e.g.…”
Section: Potential Caveats Of the Study Methodsmentioning
confidence: 76%
“…Trappability and trap diversity indices derived from standardised Capture-Mark-Recapture (CMR) studies have a moderate to good repeatability and represent reliable measures of the personality traits boldness and exploration in the habitat where the animal settled (Boon et al 2008;Boyer et al 2010;Le Coeur et al 2015;Santicchia et al 2018Santicchia et al , 2019Santicchia et al , 2020. We further refer to "Discussion" regarding possible potential caveats related to the use of these indices.…”
Section: Personality: Trappability and Trap Diversity Indicesmentioning
confidence: 99%
See 1 more Smart Citation